MENINGKATKAN KEAKTIFAN SISWA DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN THINK PAIR SHARE (TPS) - SUCI, ANANDA DE’VISKY HANGGARA; U.S, SUPARDI (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2024)
This study aims to improve the learning activity of ninth-grade junior high school students in mathematics learning through the implementation of the Think Pair Share (TPS) learning model on the material of geometric transformations. In this study, the data collected included student learning outcomes, teacher observation results, and student observation results. This research is a Classroom Action Research (CAR) conducted in two cycles. Each cycle consists of four stages: planning, action implementation, observation, and reflection. This research is considered successful if at least 85% of students get a score ? 70. Research results. From several indicators, it shows that the classical results of students who passed were 10 students or 30% of 33 students. This indicates that ninth-grade students are less enthusiastic about being actively involved in classroom learning. An analysis of the daily test results shows that classical mastery has not been achieved because it is less than 85%, so the second cycle needs to be held. Based on the second cycle of meetings 1 and 2, there was a 42% increase, so the percentage in the second cycle can be described as follows: The percentage in the first cycle was 70%. In the second cycle, there was a 56% increase in student learning outcomes compared to the first cycle, so the classical absorption of students in the second cycle was 88%. The results of the study show that the TPS model is effective in increasing student activity, as evidenced by the increase in student participation in discussions, courage in asking questions, and ability to solve geometric transformation problems. In addition, the TPS model can also help students build a better conceptual understanding. ABSTRAKPenelitian ini bertujuan untuk meningkatkan keaktifan belajar siswa kelas IX SMP dalam pembelajaran matematika melalui penerapan model pembelajaran Think Pair Share (TPS) pada materi transformasi geometri. Pada penelitian ini data yang dikumpulkan meliputi hasil belajar siswa, hasil observasi guru, hasil observasi siswa. Penelitian ini merupakan Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus. Tiap siklus meliputi 4(empat) tahap yaitu perencanaan, pelaksanaan tindakan, pengamatan (observasi) dan refleksi. Penelitian ini dikatakan berhasil apabila sekurang-kurangnya 85% siswa memperoleh nilai ? 70. Hasil penelitian. Dari beberapa indikator menunjukkan hasil klasikal siswa yang tuntas 10 siswa atau 30% dari 33 siswa. Ini menunjukkan bahwa siswa kelas IX kurang antusias sekali untuk terlibat aktif dalam pembelajaran dikelas. Analisis yang dilakukan terhadap hasil ulangan harian, menunjukkan bahwa ketuntasan klasikal belum dicapai karena kurang dari 85% sehingga perlu diadakan siklus II. Berdasarkan siklus II pertemuan 1 dan 2 ada peningkatan 42% sehingga persentase pada siklus II dapat diuraikan sebagai berikut: Persentase pada siklus 1 72% Pada siklus II ada peningkatan hasil belajar siswa dibandingkan siklus I yaitu 56% peningkatan pada siklus I sehingga daya serap klasikal siswa pada siklus II 88%. Hasil penelitian menunjukkan bahwa model TPS efektif dalam meningkatkan keaktifan siswa, ditandai dengan meningkatnya partisipasi siswa dalam diskusi, keberanian dalam bertanya, dan kemampuan dalam menyelesaikan soal-soal transformasi geometri. Selain itu, model TPS juga dapat membantu siswa dalam membangun pemahaman konsep yang lebih baik.